Analysis of Fixed Assets Management in the Legal Division at the Medan Mayor's Office - Yolanda Sambas; Rahmat Daim Harahap (Penerbit Jurnal Indonesia, 2023)
The fixed assets of the Legal Department of the Medan Mayor's Office are considered in assessing the effectiveness of a policy. This shows how efficiently the general section's delivery resources were managed by the Medan City Government last year. The Legal Department of the Medan Mayor's Office must also pay less attention to the fixed asset accounting system in order to deliver excellent Medan City Government services that are in accordance with financial management systems and procedures as well as operational standards and processes (SOP). To ensure that the budget runs smoothly and to increase the level of performance or good cooperation in the administration of these assets.